P052 Protein biomarkers identify subclinical inflammation patterns in first-degree relatives of patients with inflammatory bowel disease. (16th January 2018) - Vancamelbeke, M; Ballet, V; Ardeshir Davani, N; Van Assche, G; Ferrante, M; Cleynen, I; Vermeire, S
Abstract: Background: First-degree relatives (FDR) of patients with Crohn's disease (CD) and ulcerative colitis (UC) have the highest risk of developing inflammatory bowel disease (IBD). Although it is accepted that genetic and environmental factors contribute to the disease risk, the exact determinants are unclear. We here investigated the serological profiles of IBD patients and their healthy FDR, and compared these with non-IBD control families to study whether serum proteomics can help in defining individuals at risk. Methods: Serum and faeces were obtained from 80 individuals of 20 multiple-affected IBD families (47 IBD (38 CD/9 UC, 29.8% male, median [interquartile range, IQR] age 51.4 [42.5–59.5] years), 33 FDR (48.5% male, 45.5 [28.5–59] years)), and 39 healthy controls (HC) (53.8% male, 45.5 [27.1-56.6] years) from 8 non-IBD families. Protein biomarkers were measured in serum using the Proseek Multiplex Inflammation panel (OLINK). A total of 77 proteins (given as normalised protein expression (NPX)) were analysed following quality control and excluding markers with >75% missing data. Faecal calprotectin was measured using Bühlmann ELISA. Non-parametric statistical analyses were performed in SPSS and R with Benjamini–Hochberg correction for multiple comparisons. Protein–protein interactions were identified with STRING. Results: Diagnosis, age and family ID significantly influenced the proteomic profiles (envfit, p < 0.01). Individual comparisons according to diagnosis identified 21 protein markers with differential expression between IBD patients and HC ( p < 0.05 and fold change >1.2). Ten of these were also different in FDR compared with HC (IL8, MCP3, IL6, OSM, TGFα, HGF, ENRAGE, CASP8, IL17A, CXCL9). The top pathways associated with the IBD-specific and IBD-FDR overlapping proteins were regulation of leukocyte migration and cell chemotaxis, respectively. Calprotectin was higher in IBD patients compared with FDR and HC ( p < 0.01). The differentially expressed proteins correlated well with calprotectin, although this effect was only pronounced in patients. Nine FDR had NPX values above the median seen in IBD patients for at least 11 of the 21 differentially expressed proteins. These FDR, serologically being similar to IBD patients, did not share specific phenotypic traits nor had higher calprotectin levels, though three of them were from the same family. Conclusions: Several proteins with significant difference between IBD patients, FDR and HC were identified. The fact that some were also increased in FDR, confirms previous evidence of a subclinical state in this group. Interestingly, a subgroup also showed biomarker levels comparable to those in patients. These FDR and the identified markers merit close follow-up to confirm whether they trigger actual disease.